Pengurangan Kandungan Total Dissolved Solid (TDS), Konduktivitas dan Natural Organic Matter (NOM) pada Air Baku Bendungan Jatiluhur Menggunakan Kombinasi Membran dan Ion Exchange - Suhartono, Jono; Salsabilla, Anastasya; Rosalina, Dewi (Program Studi Teknik Kimia, Universitas Pamulang, 2024)
The escalating demand for high-quality water in industrial applications has prompted the adoption of demineralization processes as an effective solution to eliminate disruptive minerals and ions. Water, vital for process and cooling needs, must meet strict standards to avoid issues like corrosion and heavy metal pollution. Contaminants pose risks, necessitating careful attention. This study assesses demineral water requirements based on Total Dissolved Solids (TDS), conductivity, and Natural Organic Matter (NOM). Examining membrane and ion exchange technologies, including Reverse Osmosis (RO), Ultrafiltration (UF), and ion exchange resins independently and in combination, the study also explores the impact of flow rate on TDS, conductivity, and NOM. Additionally, it investigates the effect of flow rate on sampling locations at the Jatiluhur Dam. Research results highlight the effectiveness of a combined RO and resin approach, achieving an 89% reduction in TDS, 88% in conductivity, and complete NOM removal.